Teaching residents how to break bad news: piloting a resident-led curriculum and feedback task force as a proof-of-concept study. (22nd June 2021) - Sleiman, Joseph; Savage, David J; Switzer, Benjamin; Colbert, Colleen Y; Chevalier, Cory; Neuendorf, Kathleen; Harris, David
Abstract : Background: Breaking bad news (BBN) is a critically important skill set for residents. Limited formal supervision and unpredictable timing of bad news delivery serve as barriers to the exchange of meaningful feedback. Purpose of study: The goal of this educational innovation was to improve internal medicine residents' communication skills during challenging BBN encounters. A formal BBN training programme and innovative on-demand task force were part of this two-phase project. Study design: Internal medicine residents at a large academic medical centre participated in an interactive workshop focused on BBN. Workshop survey results served as a needs assessment for the development of a novel resident-led BBN task force. The task force was created to provide observations at the bedside and feedback after BBN encounters. Training of task force members incorporated video triggers and a feedback checklist. Inter-rater reliability was analysed prior to field testing, which provided data on real-world implementation challenges. Results: 148 residents were trained during the 2-hour communications skills workshop. Based on survey results, 73% (108 of 148) of the residents indicated enhanced confidence in BBN after participation. Field testing of the task force on a hospital ward revealed potential workflow barriers for residents requesting observations and prompted troubleshooting. Solutions were implemented based on field testing results. Conclusions: A trainee-led BBN task force and communication skills workshop is offered as an innovative model for improving residents' interpersonal and communication skills in BBN. We believe the model is both sustainable and reproducible. Lessons learnt are offered to aid in implementation in other settings.